Visualizing incompatibilities in phylogenetic trees using consensus outlines - Huson, Daniel H.; Cetinkaya, Banu (Frontiers in Bioinformatics, 2023)
Phylogenetic analysis frequently leads to the creation of many phylogenetic trees, either from using multiple genes or methods, or through bootstrapping or Bayesian analysis. A consensus tree is often used to summarize what the trees have in common. Consensus networks were introduced to also allow the visualization of the main incompatibilities among the trees. However, in practice, such networks often contain a large number of nodes and edges, and can be non-planar, making them difficult to interpret. Here, we introduce the new concept of a phylogenetic consensus outline, which provides a planar visualization of incompatibilities in the input trees, without the complexities a consensus network. Furthermore, we present an effective algorithm for its computation. We demonstrate its usage and explore how it compares to other methods, on a Bayesian phylogenetic analysis of languages using data from a published database, and on multiple gene trees from a published study on water lilies. Open source: https://github.com/husonlab/splitstree6 Installers: https://software-ab.cs.uni-tuebingen.de/download/splitstree6